Светофор: Стихи для детей / В. П. Михайлов - Михайлов Владимир Петрович (Мечта, 2007)
Экземпляры: ДО мл.аб. (20150820) / Инвентарный номер: 51877 / Цена: 10. 00. / Сис.шифр: С(Удм) / Авт.знак: М 69 / ГРНТИ: 17.82.93 / ББК: 84(2Рос. Удм)